Pengembangan Instrumen Penilaian Kinerja pada Praktikum Struktur dan Fungsi Sel Di SMA Negeri 1 Kota Jambi - Nugroho Budhiwaluyo; Rayandra Asyhar; Bambang Hariyadi (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2016)
This research aims to produce a final product in the form of a performance-assessment instrument on Cell Structure and Function experiment. The development model is ADDIE. Based on expert's judgment, the instrument was valid and can be tested in the field. Field-test results shown that the product performs high validity and reliability value on measuring student performance on Cell Structure and Function experiment. Therefore, it is concluded that this performance-assessment instrument theoretically and practically has a good quality for measuring student performance in both process and product performance on Cell Structure and Function experiment. Keywords: Development, Performance-Assessment Instrument, Cell Structure and Function Experiment